Reoperation for Recurrent Adrenocortical Carcinoma: A Systematic Review and Pooled Analysis of Population-Based Studies - Zhang, Fan; Liu, Zhihong; Feng, Dechao; Tang, Yongquan; Liu, Shenzhuo; Wu, Kan; Zhang, Fuxun; Zhu, Yuchun; Lu, Yiping (Frontiers in Surgery, 2022)
Background. Adrenocortical carcinoma (ACC) is a rare neoplasm having a high rate of recurrence. The aim of this study is to access the role of surgery in the clinical management of recurrent ACC. Methods. Pubmed, Embase, Web of science and Cochrane Library databases were searched and the hazard ratio were pooled. Results. Patients who underwent resection for recurrence have significantly better OS or OS after recurrence than those only received non-surgical treatments (HR 0.34, p < 0.001). Prognostic factors were identified associated with decreased OS after recurrence including multiple recurrence (HR 3.23, p = 0.001), shorter disease-free interval (HR 2.94, p < 0.001), stage III – IV of original tumor (HR 6.17, p = 0.001), Sex of male (HR 1.35, p = 0.04), and initial non-R0 resection (HR 2.13, p = 0.001). A prolonged OS after recurrence was observed in those who experienced incomplete resection (HR 0.43, 95% CI 0.31-0.52, I2 =53%) than patients who only received non-surgical treatments. In the reoperated group, patients who underwent complete resection of recurrence had a prolonged OS after recurrence than those underwent incomplete resection (HR 0.23, p = 0.004). Conclusions. We confirm the role of reoperation in the clinical management of recurrent ACC. Select patients might benefit from debulking surgery. Preoperative evaluation of the complete resection of the recurrence is the key point to decide whether patients should undergo surgery. Other prognostic factors associated with prolonged OS include single recurrence site, relatively longer disease-free interval, stage I-II of original tumor and female.